Stimulation of mGluR1/5 Improves Defective Internalization of AMPA Receptors in NPC1 Mutant Mouse. (10th October 2019) - Feng, Xiao; Yang, Fan; Rabenstein, Michael; Wang, Zhen; Frech, Moritz J; Wree, Andreas; Bräuer, Anja U; Witt, Martin; Gläser, Anne; Hermann, Andreas; Rolfs, Arndt; Luo, Jiankai
Abstract: Niemann–Pick type C1 (NPC1) disease is characterized by neurodegeneration caused by cholesterol accumulation in the late endosome/lysosome. In this study, a defective basal and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-stimulated internalization of GluR2-containing AMPA receptors in NPC1 −/− cortical neurons was detected. Our results show that the amount of cholesterol and group I metabotropic glutamate receptors (mGluR1/5) in lipid rafts of NPC1 −/− cortical tissue and neurons are decreased and their downstream signals of p-ERK are defective, which are restored by a rebalance of cholesterol homeostasis through β-cyclodextrin (β-CD) treatment. Application of 3, 5-dihydroxyphenylglycine (DHPG)—a mGluR1/5 agonist—and β-CD markedly increases the internalization of AMPA receptors and decreases over-influx of calcium in NPC1 −/− neurons, respectively. Furthermore, the defective phosphorylated GluR2 and protein kinase C signals are ameliorated by the treatment with DHPG and β-CD, respectively, suggesting an involvement of them in internalization dysfunction. Taken together, our data imply that abnormal internalization of AMPA receptors is a critical mechanism for neuronal dysfunction and the correction of dysfunctional mGluR1/5 is a potential therapeutic strategy for NPC1 disease.